The Efficacy and Treatment Fidelity of Kinesiology Taping in Conjunction With Conservative Treatment Interventions Among Individuals With Shoulder Pain: A Systematic Review with Meta-Analysis - Paul A Salamh; Christopher S Cory; William J Hanney; Haley E Condon; Xinliang Liu; Morey J Kolber (International Journal of Sports Physical Therapy)
# Purpose